Forbindelser, der er anvendelige til inhibering af ROR-Gamma-T - RICHARDSON, Timothy Ivo; MORPHY, John Richard; SAPMAZ, Selma; CLARKE, Christian Alexander; RUDYK, Helene; VAUGHT, Grant Mathews; LUGAR III, Charles Willis; STITES, Ryan Edward (2021)
The present invention provides novel ROR gamma-t inhibitors and pharmaceutical compositions thereof, formula (A).